2011
DOI: 10.1111/j.1464-410x.2010.10030.x
|View full text |Cite
|
Sign up to set email alerts
|

Varicocele as a risk factor for androgen deficiency and effect of repair

Abstract: Study Type – Therapy (case control) Level of Evidence 2b OBJECTIVE • To determine whether men with varicoceles have lower testosterone levels than those without and to ascertain if testosterone levels increase after varicocelectomy. PATIENTS AND METHODS • We measured preoperative testosterone levels in 325 men with palpable varicoceles and in 510 men with vasectomy reversal without varicoceles who served as a comparison group. • The testosterone levels between groups were compared by age. Of the men with varic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
109
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(117 citation statements)
references
References 37 publications
3
109
0
5
Order By: Relevance
“…Some studies have reported lower testosterone levels in varicocele patients. 28 Ferrucci and colleagues reported that men in the lowest quartile of total and bioavailable testosterone were more likely to have anemia. 29 Although we did not study serum testosterone lev� els in this study, the lower hemoglobin in the varicocele group could be associated with low testosterone levels.…”
Section: Coban Et Almentioning
confidence: 99%
“…Some studies have reported lower testosterone levels in varicocele patients. 28 Ferrucci and colleagues reported that men in the lowest quartile of total and bioavailable testosterone were more likely to have anemia. 29 Although we did not study serum testosterone lev� els in this study, the lower hemoglobin in the varicocele group could be associated with low testosterone levels.…”
Section: Coban Et Almentioning
confidence: 99%
“…Despite evidences suggesting that varicocele may have an impact on testicular function, in our studied population, it was not observed. Maybe the reduced number of patients with grade 3 varicocele included in the study compared to previous reports (14) can explain it. To our knowledge, no previous study has reported the relationship of ageing, obesity and varicocele.…”
Section: Discussionmentioning
confidence: 78%
“…Based on these evidences, we can assume that men with varicocele may be at risk for premature androgen deficiency and that varicocele repair may reduce this risk. A recent study showed that microsurgical varicocele ligation resulted in a significant increase in serum testosterone levels in more than two-thirds of men (14). In addition, some studies have shown that BMI has a protective effect for the development of varicocele (33,34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several reports documented a significant increase in serum testosterone post-operatively (Tanrikut et al, 2011;Hsiao et al, 2013), others failed to echo such an improvement (Pierik et al, 2001;Rodriguez Pena et al, 2009). Similarly, no statistically significant influence on serum testosterone level was detected in this cohort.…”
Section: Discussionmentioning
confidence: 99%